Assessing the psychological wellbeing and resilience of frontline health workers in Uganda: a cross-sectional study - Sarki, Ahmed M.; Atukwatse, Joseph; Mbithi, Gideon; Odero, Sabina; Namuguzi, Mary; Mutwiri, Bernard; Bitakwitse, Lestine; Wachira, Peninah; Mwangi, Kevinson; Ndirangu-Mugo, Eunice; Abubakar, Amina (Frontiers in Psychiatry, 2025)
BackgroundHealth workers in the frontline are the major drivers of health systems in low- and middle-income countries. However, these health workers face both chronic and acute shocks and stressors that expose them to mental health problems which are often overlooked. We examined the prevalence of mental health problems, correlates of psychological functioning, and resilience of frontline health workers in Uganda.MethodsWe conducted a cross-sectional study comprising 1800 frontline health workers across all regions of Uganda from August through October 2023. We used tools such as the PC-PTSD-5, PHQ9, PSS, GAD-7, Oldenburg Burnout Inventory, and CD-RISC-10 to assess PTSD, stress, anxiety, depression, burnout, resilience, and stigma. Correlates of psychological functioning comprising work engagement, quality of life, social support, and attitude were assessed. Data was analyzed using frequency analysis, where applicable, standard logistic regression models were used to examine predictors of common mental disorders among the study participants.ResultsA total of 1800 frontline health workers participated in the study, of whom 59.9% were females. The average age was 38.6 ± 11.4 years. Prevalence of depression, anxiety, and PTSD were 17.5%, 11.1% and 30.3% respectively. Community health workers had higher prevalence of depression (23.7% vs 14.4%, p<0.001), anxiety (13.3% vs 9.9% p=0.029), and PTSD (37.0% vs 26.9%, p<0.001) compared to facility-based workers respectively. Perceived stress, burnout, and negative attitude towards people with mental illness were associated with higher odds of depression. Similarly, these factors had significant association with anxiety and PTSD. Resilience, psychological wellbeing, and perceived social support were associated with lower odds of depression. Also, these factors were protective against anxiety and PTSD, except social support and resilience.ConclusionThe prevalence of PTSD, depression and anxiety is considerably high among frontline health workers in Uganda. Perceived stress, burnout, and negative attitude towards people with mental illness are associated with higher odds of mental disorders. High scores on resilience, psychological wellbeing, and perceived social support are protective against mental disorders. The mental health and well-being of frontline health workers need to be prioritized by hospital administrators, public health leaders, and policy makers especially in low- and middle-income countries.